Qualidade do solo em plantio direto sob manejo irrigado e de sequeiro - Trombetta, Lucas José (2021)
The use of irrigation in agriculture has increased in the last thirty years. The increases occurred due to population increase that pressured the supply of food, feed, fiber, and fuel, to guarantee production in weather conditions of water stress. As a result of it, there is high pressure on soils degradation and natural resources, therefore, it is essential to further studies to evaluate changes in physical, chemical, and biological properties, and consequently, in the soil quality. Therefore, the general objective of this study was to evaluate changes in soil quality in different uses and management and promote the use and validate the SMAF methodology to analyze soil quality. To meet this objective, three scientific studies were developed. The first one aimed to evaluate the influence of different soil uses and management on its physical properties; the second one aimed to evaluate the influence of soil use and management on the biological properties of the soil, and the third one testing and validating the SMAF methodology as a framework for measurement changes in soil quality caused by different soil uses and managements. The change of land use from the native environment to the cultivation environment causes degradation in the physical properties of the soil, however, the irrigation technique, in the short and long period of its use, mitigates the effects of increased density when compared to rainfed cultivation. In the biological properties, the land use change from a native environment to cultivation also causes degradation, however, when the irrigation technique is used for at least 25 years, it leads to an improvement in these properties, especially in the Carbon attribute of the biomass microbial (BMS-C) and basal soil respiration (RBS). There was an increase of 21.27% in the irrigated area in relation to the dryland planting. The SMAF methodology proved to be an effective framework in the assessment of soil quality, demonstrating that the environments do not operate at their maximum capacity. However, irrigated planting in both areas was higher than dry planting and native environment in the general quality index of the soil. Therefore, the irrigated planting proved to be an alternative to alleviate degradations in soil quality in cultivation environments.